Anambra State Agricultural Development Project / Project services, civil works and organization, economic evaluation (Ibadan Grrenlands Agro-Industries Co Ltd., 1982)
A three volume report prepared in accordance with an agreement signed on 28th April 1980 between Federal Ministry of Agriculture and Greenlands Agro-Industrial Limited in collaboration with Tahal Consult (Nigeria) Limited. The report contains findings of a feasibility study for the establishment of the Anambra State Agricultural Development project. Emphasis is placed on increasing smallholder production from the state's 368,000 farming families who at the time of the report cultivate some 400,000 hectare, approximately 23 percent of the total area of the State.
lje 04/07/17
Loans
Keywords: Agricultural Development-Anambra State-Nigeria; Anambra state - Nigeria